Pendekatan, Tantangan, dan Strategi dalam Pembelajaran Bahasa Arab di Lembaga Pendidikan - Ardia Pramesti Regita cahyani (Al-Qalam: Jurnal Pendidikan Bahasa Arab, 2025)
Teaching translation is a field that continues to evolve along with the need for cross-lingual and cross-cultural communication. This article discusses various effective approaches, challenges, and strategies in translation learning. Based on a literature review and empirical research, it was found that a competency-based approach—covering linguistic, cultural, technical, and strategic aspects—is the most widely recommended method for improving translation quality. In addition, technology integration, such as computer-aided translation tools (CAT tools) and machine translation (MT), provides efficiency but also requires critical assistance to avoid over-dependence. Collaborative learning methods, such as problem-based learning (PBL) and peer feedback, have been proven to improve students' analytical skills and creativity. However, challenges such as lack of understanding of specialized fields (law, medical) and classroom dynamics remain barriers. This study concludes that effective teaching of translation must incorporate multidisciplinary approaches, judicious use of technology, and continuous evaluation through structured feedback. The implication is that educators need to design an adaptive and contextual curriculum to meet the learning needs of the digital era.